Entropy Analysis of a Valveless Piezoelectric Pump With Hyperbolic Tubes - Yang, Qing; Chen, Jun (Frontiers in Energy Research, 2022)
In order to solve the problems of large reflux and low output performance of the valveless piezoelectric pump with conical tubes, the valveless piezoelectric pump with hyperbolic tubes was proposed. However, the previous research only paid attention to the difference of forward and reverse flow resistance inside the tubes. For this reason, the prototypes of conical tube valveless piezoelectric pump and hyperbolic tubes valveless piezoelectric pump were fabricated in this paper. The maximum output flow rate of the hyperbolic tubes valveless piezoelectric pump is 54mL/min, and the output performance of the valveless piezoelectric pump with hyperbolic tubes is better than that of the valveless piezoelectric pump with conical tubes. Subsequently, this paper numerically calculated the size and position of the hyperbolic tubes entropy generation based on the entropy generation theory. The results show that the entropy production rate of the hyperbolic tube is significantly lower than that of the conical tube, which is consistent with the flow test results. This research analyzed the energy loss inside the valveless piezoelectric pump by using the entropy generation theory, and provided a new design and research method for improving the output performance of the valveless piezoelectric pump in the future.